Perilaku Ibu Terhadap Pertumbuhan Balita Dalam Permasalahan Stunting Dan Pencegahannya Di Desa Torosiaje Jaya - Husain, Rustam I.; Umar, Masri Kudrat; Lamatenggo, Nina (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2019)
The growth process experienced by toddlers is a cumulative result since the toddler was born. From various studies on stunting and existing literature it is known that in addition to infection, stunting is also associated with nutritional deficiencies (micronutrients and macronutrients). There are several nutrients related to stunting such as protein, iron, zinc, calcium, and vitamins D, A and C. at the family level, especially for poor families, low family access to basic health services, and disparities between provinces that need to be addressed specifically for problems in vulnerable areas.6,9,10 Stunting is a sensitive indicator for poor socioeconomic conditions and predictors for long-term morbidity and mortality. Stunting in early childhood is reversible. 11